When pathology defies expectations: a surprising diagnosis of prostatic leiomyosarcoma - Shah, Abhijit; Singh, Anshuman; Gali, Kasi V.; Gunashekaran, Vijay; Hegde, Padmaraj (International Journal of Research in Medical Sciences, 2023)
Prostatic leiomyosarcoma is an exceedingly rare malignant tumour arising from smooth muscle cells in the prostate gland. It ranks quite low down on the possible differentials of bladder outlet obstruction. We present a case of a 38-year-old male who initially presented with acute urinary retention and was subsequently diagnosed with prostatic leiomyosarcoma. Following histopathological confirmation, metastatic work-up was performed and patient planned for radiation and surgical cure. Patient on follow-up is well and has resumed normal daily work. This case report aims to increase awareness of this rare malignancy, discuss the diagnostic challenges faced with a highly common clinical spectrum at the onset, present the treatment strategies employed, and discuss the patient’s clinical outcomes. We emphasise the importance of reporting rare cases like this to contribute to the existing literature and enhance the understanding of prostatic leiomyosarcoma.